Whole exome sequencing identifies a novel homozygous frameshift mutation in the ASPM gene, which causes microcephaly 5, primary, autosomal recessive [version 1; referees: 2 approved] - Desaraju Suresh Bhargav; N. Sreedevi; N. Swapna; Soumya Vivek; Srinivas Kovvali (F1000Research, 2017)
Microcephaly is a genetically heterogeneous disorder and is one of the frequently notable conditions in paediatric neuropathology which exists either as a single entity or in association with other co-morbidities. More than a single gene is implicated in true microcephaly and the list is growing with the recent advancements in sequencing technologies. Using massive parallel sequencing, we identified a novel frame shift insertion in the abnormal spindle-like microcephaly-associated protein gene in a client with true autosomal recessive primary microcephaly.  Exome sequencing in the present case helped in identifying the true cause behind the disease, which helps in the premarital counselling for the sibling to avoid future recurrence of the disorder in the family.